Losing sleep by staying up late leads adolescents to consume more carbohydrates and a higher glycemic load. Issue 3 (17th December 2021) - Duraccio, Kara McRae; Whitacre, Catharine; Krietsch, Kendra N; Zhang, Nanhua; Summer, Suzanne; Price, Morgan; Saelens, Brian E; Beebe, Dean W
Abstract: This study examined how short sleep impacts dietary consumption in adolescents by testing whether experimentally shortening sleep influences the amount, macronutrient content, food types, and timing of food consumed. Ninety-three adolescents completed a within-subjects crossover paradigm comparing five nights of short sleep (6.5-hour sleep opportunity) to five nights of Healthy Sleep (9.5-hour sleep opportunity). Within each condition, adolescents completed three multiple-pass dietary recalls that recorded the types, amount, and timing of food intake. The following outcomes were averaged across days of dietary recall within condition: kilocalories, grams of carbohydrates, fat, protein, and added sugars, glycemic load of foods, and servings of specific types of foods (low-calorie drinks, sweetened drinks, fruits/vegetables, meats/proteins, processed snacks, "fast food" entrees, grains, and sweets/desserts). Timing of consumption of kilocalorie and macronutrient outcomes were also examined across four noncumulative time bins: 06:00–10:59, 11:00–15:59, 16:00–20:59, and 21:00–01:00. Adolescents slept 2 h and 20 min longer in Healthy Sleep than in Short Sleep ( p < .0001). While in Short Sleep, adolescents ate more grams of carbohydrates ( p = .031) and added sugars ( p = .047), foods higher in glycemic load ( p = .013), and servings of sweet drinks ( p = .023) and ate fewer servings of fruits/vegetables ( p = .006) compared to Healthy Sleep. Differences in consumption of kilocalories, fat, and carbohydrates emerged after 9:00 pm ( p s = .012, .043, .006, respectively). These experimental findings suggest that adolescents who have insufficient sleep exhibit dietary patterns that may increase the risk for negative weight and cardiometabolic outcomes. Future health promotion efforts should include promoting optimal sleep to increase healthy dietary habits.